UJI TOKSIK SUSPENSI SEL PUNCA CD34+ MANUSIA PADA TIKUS SPRAGUE DAWLEY (SD) - Supartono, Basuki (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2014)
Introduction :  Research of CD34+ cells intervention to rats is not yet done. This researchis the latest research which investigated the toxic reaction of CD34+ hematopoietic stem cell intervention in non engineered rats.Methods : 3 Sprague Dawley rats, male, 7 months, 285+18,5 g. Rat 1 : received intraartricular injection of human peripheral blood CD34+ cells (105 cells). Rat 2 : received intraartricular injection of human cord blood CD34+ cells (105 cells). Rat 3 : received intraartricular injection of human cord blood CD34+ cells (106 cells), hyaluronic acid and grown factors. All rats were examined hematological, blood chemistry parameters and microscopic of the liver and kidney.Result : All rats showed good condition. There is slight increasing parameter in hematological and blood chemistry but liver and kidney in normal microscopic condition. No hiperacute rejection reaction : edema, systemic bleeding. There is no hyper acute and acute reaction.Conclusion :  Human CD34+ cells suspension with or without scaffold and growth factors does not cause toxicity reaction in naïve Sprague Dawley rats.